2016
DOI: 10.1049/iet-nbt.2015.0104
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of silver nanoparticles from Cassia fistula (Linn.): In vitro assessment of their antioxidant, antimicrobial and cytotoxic activities

Abstract: The present study reports on biogenic-synthesised silver nanoparticles (AgNPs) derived by treating Ag ions with an extract of leaf, a popular Indian medicinal plant found in natural habitation. The progress of biogenic synthesis was monitored time to time using a ultraviolet-visible spectroscopy. The effect of phytochemicals present in including flavonoids, tannins, phenolic compounds and alkaloids on the homogeneous growth of AgNPs was investigated by Fourier-transform infrared spectroscopy. The dynamic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…Current investigation result of antioxidant potential of E. suberosa offers an affirmative report toward hypothetical mechanism about involvement of antioxidant molecules from the leaf extract in the biogenic synthesis of silver nanoparticles. Previous research study revealed that, plant contains phenolic and flavonoids possess high antioxidant capabilities and hence biosynthesis of nanoparticles (Mohanta et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current investigation result of antioxidant potential of E. suberosa offers an affirmative report toward hypothetical mechanism about involvement of antioxidant molecules from the leaf extract in the biogenic synthesis of silver nanoparticles. Previous research study revealed that, plant contains phenolic and flavonoids possess high antioxidant capabilities and hence biosynthesis of nanoparticles (Mohanta et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we observed the appearance of absorption peak at ~428 nm. Previous study reported that AgNPs give absorption peak at 420–450 nm as a result of its surface plasmon resonance (SPR) character (Mohanta et al, 2016; Nayak et al, 2016). In our study, the observed absorption peak at 428 nm further confirms the biosynthesis of Ag nanoparticles (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now a days, various plant parts like bark, leaf, fruit, stem and seed extracts have been successfully used for the synthesis of metal nanoparticles (Mittal et al, 2013). Among different metal nanoparticles, silver (Ag) nanoparticles have been used enormously due to their potential anti-bacterial (Mohanta et al, 2016a,b), anti-fungal and anti-proliferative activity (Kim et al, 2007; Nayak et al, 2015). Due to the excellent antimicrobial properties, the silver (Ag) nanoparticles have been extensively used in food packaging, food and seed preservation, biofertilizers, cosmetics and medicines (Marambio-Jones and Hoek, 2010; Dipankar and Murugan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, when the culture supernatant is treated with aqueous solution of silver nitrate, then it forms silver nanoparticles extracellularly [10]. In the recent past, silver nanoparticles have gainedattention of researchers worldwide due to their potential antimicrobial activities [8,[11][12][13]. The properties of silver nanoparticles have made them applicable in severalareassuch as biomedical, drug delivery, water treatment, agricultures, etc.…”
Section: Introductionmentioning
confidence: 99%